2018
DOI: 10.11606/s1518-8787.2018052001199
|View full text |Cite
|
Sign up to set email alerts
|

What is the importance of vaccine hesitancy in the drop of vaccination coverage in Brazil?

Abstract: The successful Programa Nacional de Imunizações do Brasil (Brazilian National Immunization Program) has been experiencing a major challenge with regard to vaccination coverage for children, which has been dropping. Several aspects are related, but certainly vaccine hesitancy has been strengthening itself as one of the main concerns of Brazilian public administrators and researchers. Vaccine hesitancy is the delay in acceptance or refusal despite having the recommended vaccines available in health services, bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
0
56

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(195 citation statements)
references
References 29 publications
4
95
0
56
Order By: Relevance
“… Adam (2020) Perceived Behavioral Control PBC1 The preventive protocols are completely up to me. Sato (2018) PBC2 I think preventive protocols are easy to be implemented. Shen et al (2020) PBC3 I am confident that I can prevent getting infected by COVID -19.…”
Section: Methodsmentioning
confidence: 99%
“… Adam (2020) Perceived Behavioral Control PBC1 The preventive protocols are completely up to me. Sato (2018) PBC2 I think preventive protocols are easy to be implemented. Shen et al (2020) PBC3 I am confident that I can prevent getting infected by COVID -19.…”
Section: Methodsmentioning
confidence: 99%
“…New vaccines were later included to control infections by Haemophilus influenzae type b, rotavirus and pneumococcal, making the vaccination schemes more complex [5,6]. Over the last four decades, Brazil has made a tremendous progress in improving levels of vaccination coverage [6], however, estimates from the National Immunization System showed that coverage with key vaccines has decreased from 2014 onwards [7,8]. A previous study from Pelotas analyzed trends in immunization coverage over a 33-year period and observed a major increase in coverage from 1980 to 1993, followed by a slightly decrease from 1993 to 2004, and further declines from 2004 to 2015 [9].…”
Section: Introductionmentioning
confidence: 99%
“…Despite advances and international recognition, PNI has faced challenges, such as the recent drop in vaccine uptake rates and their considerable differences between regions 19 . The decrease in vaccine uptake rates in Brazil is multifactorial.…”
Section: Introductionmentioning
confidence: 99%